Current status of palliative care services in Indonesia: a literature review. (11th January 2016) - Rochmawati, Erna; Wiechula, Rick; Cameron, Kate
Abstract : Aim: To review healthcare literature in relation to the provision of palliative care in Indonesia and to identify factors that may impact on palliative care development. Background: People living with life‐limiting illness benefit from access to palliative care services to optimize quality of life. Palliative care services are being expanded in developing countries but in Indonesia such services are in their infancy with many patients with life‐limiting illnesses having access to appropriate health care compromised. Methods: Relevant healthcare databases including CINAHL, PubMed, Science Direct and Scopus were searched using the combinations of search terms: palliative care, terminal care, end‐of‐life care, Indonesia and nursing. A search of grey literature including Internet sites was also carried out. Results: Nine articles were included in the review. Facilitating factors supporting the provision of palliative care included: a culture of strong familial support, government policy support, volunteering and support from regional organizations. Identified barriers to palliative care provision were a limited understanding of palliative care among healthcare professionals, the challenging geography of Indonesia and limited access to opioid medications. Conclusions: There are facilitators and barriers that currently impact on the development of palliative care in Indonesia. Strategies that can be implemented to improve palliative care include training of nurses and doctors in the primary care sector, integrating palliative care in undergraduate medical and nursing curriculum and educating family and community about basic care. Nurses and doctors who work in primary care can potentially play a role in supporting and educating family members providing direct care to patients with palliative needs.